The effects of informal settlements on environmental management in Temeke Municipality - Mwamhanga, Evaristo B. (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science in Environmental Management (MSc. EM) of Mzumbe University